Anthropogenic emission inventories in China: a review. Issue 6 (26th December 2017) - Li, Meng; Liu, Huan; Geng, Guannan; Hong, Chaopeng; Liu, Fei; Song, Yu; Tong, Dan; Zheng, Bo; Cui, Hongyang; Man, Hanyang; Zhang, Qiang; He, Kebin
Abstract: The development of reliable anthropogenic emission inventories is essential for both understanding the sources of air pollution and designing effective air-pollution-control measures in China. However, it is challenging to quantify emissions in China accurately, given the variety of contributing sources, the complexity of the technology mix and the lack of reliable measurements. Over the last two decades, tremendous efforts have been made to improve the accuracy of emission inventories, and significant improvements have been realized. More reliable statistics and survey-based data have been used to reduce the uncertainties in activity rates and technology distributions. Local emission factors and source profiles covering various sources have been measured and reported. Based on these local databases, improved emission inventory models have been developed for power plants, large industrial plants and the residential, transportation and agricultural sectors. In this paper, we review the progress that has been made in developing inventories of anthropogenic emissions in China. We first highlight the major updates that have been made to emission inventory models and the underlying data by source category. We then summarize the sector-based estimates of emissions of different species contained in current inventories. The progress that has been made in the development of model-ready emissions is also presented. Finally, we suggest future directions for further improving the accuracy of emission inventories in China.